Anatomical study of the seed of andiroba (Carapa guianensis) through stereo and scanning electron microscopy - SILVA, Bruna Aparecida da; SCUSSEL, Vildes Maria; TRIBUZI, Giustino (Acta amazonica, 2025)
ABSTRACT The points of susceptibility of seeds to deterioration are important factors, especially when stored in hot and humid tropical conditions. The seeds of andiroba (Carapa guianensis) are an important resource for Amazonian traditional communities, as the oil extracted from the seeds is widely used in popular medicine and the cosmetic industry. Yet andiroba seeds are subject to fungal spoilage, which affects the quality of the oil. We analyzed the morpho-histological characteristics of whole andiroba seeds by stereo and scanning electron microscopy to identify susceptibility points to fungi. The shell (tegument), a thick lignin-rich, protective wall structure, varied in the type and number of tissue layers, with polygonal and long shaped cells presenting pores (plasmodesmata). The junction of the three faces of the seeds at the top formed a relatively tight small cavity, the micropyle, rich in vascular bundles of helically and tracheid-shaped vessels. An interchange channel from the pod through the micropyle to the inner seed is formed between the shell and a thin brown skin towards the cotyledons, with its surface covered with adhered residues of dry placental tissue. The seed cotyledons (cross and longitudinal sections), presented different cell layers containing randomly distributed lipid droplets. We concluded that the highly irregular surface of the micropyle and channel at the seed top, which forms deep recesses and accumulates tissue residues, presents the righest risk for fungi conidia deposition and/or moisture absorption, which leads to spoilage. RESUMO Os pontos de suscetibilidade das sementes à deterioração são fatores importantes, especialmente quando armazenadas em condições tropicais quentes e úmidas. As sementes de andiroba (Carapa guianensis) são um recurso importante para as comunidades tradicionais amazônicas, pois o óleo extraído das sementes é amplamente utilizado na medicina popular e na indústria de cosméticos. Porém, as sementes de andiroba são suscetíveis à deterioração por fungos, o que afeta a qualidade do óleo. Nós analisamos as características morfo-histológicas de sementes inteiras de andiroba por meio de microscopia estereoscópica e eletrônica de varredura para identificar pontos de suscetibilidade a fungos. A casca (tegumento), uma estrutura protetora espessa e rica em lignina, variou no tipo e no número de camadas de tecido, com células de formato poligonal e alongado apresentando poros (plasmodesmos). A junção das três faces da semente no topo formou uma pequena cavidade relativamente fechada, o micrópilo, rico em feixes vasculares com vasos em espiral e de formato traqueidal. Um canal de intercâmbio da vagem até a semente interna é formado entre a casca e uma fina membrana marrom em direção aos cotilédones, cuja superfície é coberta por resíduos aderidos de tecido placentário seco. Os cotilédones da semente (seções transversais e longitudinais) apresentaram diferentes camadas celulares contendo gotas lipídicas distribuídas aleatoriamente. Concluímos que a superfície altamente irregular do micrópilo e o canal no topo da semente, que formam recessos profundos e acumulam resíduos de tecido, apresentam maior risco para a deposição de conídios de fungos e/ou absorção de umidade, levando à deterioração.